COMMUNITY CONNECTIONS: LINKING AFFORDABLE HOUSING AND ACADEMIA. (11th November 2018) - Phillips, K
Abstract: As people live longer and baby boomers grow older, the demand for affordable, supportive, and high-quality housing will continue to increase. However, the lack of affordable and accessible housing options that support aging-in-place is a major barrier to rebalancing the delivery of community-based services and care. In order to prevent social isolation and better serve seniors, we investigated the effect of pairing an affordable senior housing community in Richmond, VA, with Virginia Commonwealth University. Through research initiatives, health education, and social engagement, VCU supported positive aging-in-place and provided services and programs that addressed the needs of the residents while also providing them with opportunities to volunteer with and for the programs. This partnership also supported the engagement of the broader community and the sustainability of supportive housing. Discussion will highlight effective strategies used within this intervention.